Challenges And Solutions In Ocr Of Handwritten Bangla Documents (Journal of Namibian Studies : History Politics Culture, 2023)
Optical character recognition (OCR) is a process of converting analogue documents into digital using document images. Currently, many commercial and non-commercial OCR systems exist for both handwritten and printed copies for different languages. Despite this, very few works are available in case of recognizing Bengali words. Among them, most of the works focused on OCR of printed Bengali characters. While OCR for printed texts has made significant progress, the OCR of handwritten documents poses unique challenges, particularly for scripts with complex character shapes and variations, such as Bangla. This research paper explores the issues related to OCR of handwritten Bangla documents and proposes potential solutions to improve the accuracy and efficiency of the recognition process.